Electrochemical hydrogen peroxide sensor based on cobalt phthalocyanine captured in polyaniline film on a glassy carbon electrode - (:unkn) unknown (WORLD SCI PUBL CO INC, 2012)
This work demonstrated preparation, characterization, and application of a cobalt phthalocyanine based enzymeless/mediatorless hydrogen peroxide sensor. The cobalt phthalocyanine (CoPc) was retained in polyaniline (PANI) film on a glassy carbon electrode during electrochemical polymerization of aniline and consequently a novel composite electrode (GCE/PANI/CoPc) for the electrochemical sensor application was constructed. The CoPc functionalized composite electrode, GCE/PANI/CoPc, was evaluated by voltammetry, electrochemical impedance spectroscopy, and UV-vis spectroscopy. The results displayed retaining of the CoPc molecules in the PANI film on the GCE electrode. Presence of CoPc in PANI increased conductivity of the composite on the electrode. Sensing performance of the GCE/PANI/CoPc composite electrode to H2O2 were evaluated in detail with respect to the selectivity, reproducibility, repeatability, stability, linear concentration range, and sensitivity with voltammetric and double potential step chronoamperometric techniques. The GCE/PANI/CoPc composite electrode gives a linear range for H2O2 between 2 and 18 mu M H2O2 with sensitivities of 1.55 A.M-1 during the cathodic SWV scan and with sensitivities of 4.01 A.M-1 during the anodic SWV scan. A direct application of the sensor was performed in a real working condition, for the detection of hydrogen peroxide produced from the reaction between the glucose and glucose oxidase enzyme.
Keywords: cobalt phthalocyanine; hydrogen peroxide; enzymeless sensor; square wave voltammetry; TRANSITION-METAL IONS; AMPEROMETRIC BIOSENSORS; OXYGEN REDUCTION; THIN-FILM; RECEPTORS; RECOGNITION; CATIONS; BEARING; ELECTROPOLYMERIZATION; ELECTROCATALYSIS